THE DEVELOPMENT OF STUDENT WORKSHEETS (LKPD) WITH A SCIENTIFIC APPROACH ON THE MATERIAL OF AKIDAH AKHLAK AT THE CLASS VIII OF MADRASAH TSANAWIYAH - Muhammad Ansari; Zulfatmi Budiman; Realita Nurdin; Hasan Basri; Qudwatin Nisak (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
The purpose of this study was to create a scientific-based Student Worksheets (LKPD) on the subject matter of Akidah Akhlak grade 8 Madrasah Tsanawiyah by knowing the level of feasibility and the teacher's response to the product being developed. This study uses research and development methods with the ADDIE model, including five steps: Analysis, Design, Development, Implementation, and Evaluation which are modified according to the conditions at the time of the study. Data collection techniques used validation sheets and teacher response questionnaires. The percentage of the LKPD feasibility validation stage is from the material field, it gets 98.8%, the media field gets 90%, the language field gets 75%, and the scientific approach field gets 98.3%. The total average value of the overall percentage of validators is 90.5% with the criteria of Very Eligible. While the results of the questionnaire responses to Akidah Akhlak teachers obtained a total percentage of 88.4% with very good criteria for the scientific-based Akidah Akhlak LKPD product. So, it can be concluded that this scientific-based LKPD can be used as teaching material in the learning process in the classroom.